Occurrence and physico-chemical properties of aplite-derived kaolin from eastern Kinta valley, Malaysia (Kuwait Journal of Science)
Kaolin from eastern Kinta Valley was studied for its geological, geochemical, mineralogical, and textural characteristics. Research was conducted on kaolinitic occurrence from three locations, and the samples were subjected to analysis by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), particle size distribution (PSD), X-ray fluorescence (XRF), and differential thermal analysis and thermogravimetry (DTA/TG). Field studies indicate that the aplite is originally embedded into a northwest trending fault and is kaolinized by a latter fault reactivation and hydrothermal activities related to the hydrothermal cassiterite mineralization. XRD and FTIR analyses reveal that the clays are well-ordered kaolinite and halloysite with minor illite present. Geochemically, the kaolin displays low content (<0.4%) of Fe + Ti and 0.7% alkali. The washed kaolin shows composition approaching ideal kaolin. However, the raw clay consists of a 42–77% clay fraction, with quartz as the prime coarser constituent. The clay fractions are typically soft kaolin with coarse kaolinite stacks (d50 = 7–8 μm), except for a sample with a fine halloysite fraction. This study presents a new mode of kaolin occurrence in Malaysia, with the potential to be developed into a new kaolin mining region. © 2025 The Authors